CO2-emissions form Norwegian oil and gas extraction - Ekaterina Gavenas; Knut Einar Rosendahl; Terje Skjerpen (Statistics Norway, Research Department, 2015)
Emissions from oil and gas extraction matter for the lifecycle emissions of fossil fuels, and account for significant shares of domestic emissions in many fossil fuel exporting countries. In this study we investigate empirically the driving forces behind CO2-emission intensities of Norwegian oil and gas extraction, using detailed field-specific data that cover all Norwegian oil and gas activity. We find that emissions per unit extraction increase significantly as a field's extraction declines. Moreover, emission intensities increase significantly with a field's share of oil in total oil and gas reserves. We also find some indication that oil and CO2-prices may have influenced emission intensities on the Norwegian continental shelf.
Keywords: C23; L71; Q54; 330; CO2-emissions; Oil and gas extraction; Panel data estimation.